Increase of In-Situ Measured Shear Wave Velocity in Sands with Displacement Pile and Stone Column Inclusions - Toha, Franciscus Xaverius (Institut Teknologi Bandung, 2017)
AbstractSeismic downhole and MASW measurements were conducted at a potentially liquefiable site, where PC piles and stone column inclusion were provided to remediate the foundation soil. The selected site is part of a refinery located in high seismicity zone. The seismic measurements were done prior and after the PC piles and stone columns were installed. The densification, reinforcing, and dissipation contribution to the overall mitigation was elaborated herein. The measurement results are essentially consistent with the most recent theoretical developments and indicate that the strengthening due to mitigation is higher than predicted.AbstrakPada situs yang berpotensi likuifaksi dengan sisipan tiang pancang PC dan tiang batu, dilakukan pengukuran seismik turun lubang dan MASW. Lokasi yang dipilih adalah bagian dari sebuah kilang minyak yang terletak dalam zona gempa tinggi. Pengukuran seismik dilakukan sebelum dan sesudah pemancangan tiang PC dan tiang batu. Uraian mendalam tentang sumbangan pemadatan, perkuatan dan disipasi terhadap keseluruhah mitigasi disampaikan di sini. Hasil pengukuran pada dasarnya konsisten dengan perkembangan teoritis terkini dan menunjukkan bahwa perkuatan akibat mitigasi masih di atas perkiraan.